Emosi dan Hubungan Antar Sebaya pada Anak Tunalaras Usia Sekolah antara Terapi Musik Klasik (Mozart) dan Murrotal (Surah Ar-Rahman) - Padila Padila; Setiawati Setiawati; Iin Inayah; Henny Suzana Mediani; Chatarina Suryaningsih (Jurnal Keperawatan Silampari, 2020)
This study aims to analyze the differences in the effectiveness of traditional music therapy (Mozart) and murrotal therapy (surah ar-Rahman) on emotional changes and peer relationships in school-aged children in SDN 1 Noman Musi Rawas Utara. The design of this study uses a quasi-experimental, pre-test, and post-test design. The results of the survey, there are differences in traditional music therapy (Mozart) and murrotal (ar-Rahman) on emotional changes and peer relationships in children with disabilities. There was a significant difference in the mean tunalaras after being given the classic intervention (Mozart) week 5, which was 9.06. In contrast, after being given the murrotal intervention (Ar-Rahman) week 5, it fell to 2.24. the mean difference in the score of tunalaras was 6.82 times, Conclusions, Murrotal therapy (Ar-Rahman) 6-7 times faster to reduce emotionally and improve peer relations in children with tunalaras compared to traditional music therapy (Mozart). Keywords: Tunalaras Children, Murrotal (Surah Ar-Rahman), Classical Music (Mozart)